(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The binding of Ketorolac and Omeprazole to bovine serum albumin (BSA) was studied by equilibrium dialysis method followed by UV spectroscopy. Warfarin and Diazepam were used as site-I and site-II specific probe, respectively. The binding of Ketorolac and Omeprazole was characterized by two sets of association constant: high affinity association constant (K1) with low capacity binding site (n1) and low affinity association constant (K1) with high capacity binding site (n1). In this study, n1 and n1 values were found to be 0.25 ± 0.006 and 1.8 ± 0.025 for Ketorolac and 0.22 ± 0.030 and 1.3±0.035 for Omeprazole at pH 7.4 and 37°C, respectively. At the same condition, the values of K1 and K1 for Ketorolac were found to be 0.624 ± 0.033 ?M-1 and 0.133 ± 0.023 ?M-1 and that of Omeprazole were 0.51 ± 0.001 ?M-1 and 0.28 ± 0.005 ?M-1, respectively. Site specific probe displacement studies implied that both Ketorolac and Omeprazole bind predominantly to site-II, the Diazepam site. In the present study, both Ketorolac and Omeprazole increased the free fraction of each other when they simultaneously bound to BSA. They compete for a common binding site on the albumin molecule, thereby free fraction of both the drugs was increased as compared to the level obtained when the drugs were given individually. We, thus, conclude that during concurrent administration of Ketorolac and Omeprazole adequate precautions should be taken. However, further studies are needed on in-vivo model to substantiate the findings from in-vitro experiments. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22323 Bangladesh Pharmaceutical Journal 17(1): 92-98, 2014